2007
DOI: 10.4049/jimmunol.178.5.3099
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Antibody-Dependent Cellular Cytotoxicity Mechanism Involved in Defense against Malaria Requires Costimulation of Monocytes FcγRII and FcγRIII

Abstract: Clinical experiments have shown that the Ab-dependent cell-mediated inhibition of Plasmodium falciparum is a major mechanism controlling malaria parasitemia and thereby symptoms. In this study, we demonstrate that a single merozoite per monocyte (MN) is sufficient to trigger optimal antiparasitic activity. Using particulate Ag as pseudomerozoites, we show that only Ags, and no other parasite-derived factor, are required to trigger MN activation and that a single Ag is as potent as the complex combination of Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 59 publications
6
76
1
Order By: Relevance
“…The IgG3 type of response was more prevalent than the IgG1 response, whereas the levels of both were equivalent. The importance of this finding is related to previous studies showing that IgG antibodies either mediating parasite killing in vitro or associated with protection in vivo are restricted to the IgG1 and IgG3 subclasses (4,16,20,30). In agreement with this, all 24 peptides were indeed found to define antigenic determinants able to trigger the antiparasitic ADCI mechanism.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The IgG3 type of response was more prevalent than the IgG1 response, whereas the levels of both were equivalent. The importance of this finding is related to previous studies showing that IgG antibodies either mediating parasite killing in vitro or associated with protection in vivo are restricted to the IgG1 and IgG3 subclasses (4,16,20,30). In agreement with this, all 24 peptides were indeed found to define antigenic determinants able to trigger the antiparasitic ADCI mechanism.…”
Section: Discussionsupporting
confidence: 80%
“…The negative control was IgG from a pool of French donors with no malaria history (N-IgG). Peripheral blood mononuclear cells (PBMC) from healthy French donors were prepared and cryopreserved as previously described (20). For the ADCI assay, PBMC were rapidly thawed at 37°C and assessed for viability by trypan blue exclusion.…”
Section: Methodsmentioning
confidence: 99%
“…This was as high as 74% SGI at 1:100 dilutions and still significant at 46% at 1:1,000 dilutions. The degree of inhibition obtained with affinity-purified human antibodies was also very high and comparable to that of pooled Igs of adults living in areas of Africa where malaria is endemic (7,12,20). These results, obtained with two different adjuvants in animal models and with naturally induced antibodies from humans, suggest that the primary mechanism of protection employed by P27A antibodies is likely to be in cooperation with MN.…”
Section: Resultssupporting
confidence: 54%
“…One of the principal mechanisms that mediates clinical malaria in humans has been shown to be the cooperation between cytophilic antibodies and MN (7,20). The in vitro ADCI assay, based on this mechanism, has been used to assess the capacity of purified human and murine antibodies to inhibit malaria parasite growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These antibodies were tested in mice transgenic for human Fc-receptors challenged with transgenic rodent malaria parasites (expressing PfMSP-1p19) in an effort to evaluate the role of antibodies in protection. Another study demonstrated that the activation of monocytic cells requires two distinct Fcγ receptors (FcγRII and FcγRIII) simultaneously engaged by a least two cytophilic IgG molecules, which are part of the same immune complexes (Jafarshad et al, 2007). Finally, the concept of the contribution of Fc receptors in natural immunity is supported by epidemiological studies (Shi et al, 2001;Israelsson et al, 2008;Leoratti et al, 2008).…”
Section: Functional Assays To Evaluate Antibody Dependent Cellular Cymentioning
confidence: 96%